Platelet Activation and Apoptosis Modulate Monocyte Inflammatory Responses in Dengue - Hottz, Eugenio D; Medeiros-de-Moraes, Isabel M; Vieira-de-Abreu, Adriana; de Assis, Edson F; Vals-de-Souza, Rogério; Castro-Faria-Neto, Hugo C; Weyrich, Andrew S; Zimmerman, Guy A; Bozza, Fernando A; Bozza, Patrícia T (The Journal of immunology (1950), 2014)
Dengue is the most prevalent human arbovirus disease in the world. Dengue infection has a large spectrum of clinical manifestations, from self-limited febrile illness to severe syndromes accompanied by bleeding and shock. Thrombocytopenia and vascular leak with altered cytokine profiles in plasma are features of severe dengue. Although monocytes have been recognized as important sources of cytokines in dengue, the contributions of platelet–monocyte interactions to inflammatory responses in dengue have not been addressed. Patients with dengue were investigated for platelet–monocyte aggregate formation. Platelet-induced cytokine responses by monocytes and underlying mechanisms were also investigated in vitro. We observed increased levels of platelet–monocyte aggregates in blood samples from patients with dengue, especially patients with thrombocytopenia and increased vascular permeability. Moreover, the exposure of monocytes from healthy volunteers to platelets from patients with dengue induced the secretion of the cytokines IL-1β, IL-8, IL-10 and MCP-1, whereas exposure to platelets from healthy volunteers only induced the secretion of MCP-1. In addition to the well-established modulation of monocyte cytokine responses by activated platelets through P-selectin binding, we found that interaction of monocytes with apoptotic platelets mediate IL-10 secretion through phosphatidylserine recognition in platelet–monocyte aggregates. Moreover, IL-10 secretion required platelet–monocyte contact but not phagocytosis. Together, our results demonstrate that activated and apoptotic platelets aggregate with monocytes during dengue infection and signal specific cytokine responses that may contribute to the pathogenesis of dengue.